ระบบบริหารโรงเรียนราษฎร์ฝ่ายคริสตศาสนาในพระนครและธนบุรี - จงกลณี นาคสมบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1971)
The purposes of the Study 1. To investigate the philosophy and objectives of the parochial private schools in Bangkok and Thonburi. 2. To study the administrative systems of parochial private schools in regard to the following: 2.1 Organizational structure 2.2 Control 2.3 Management and operation 2.4 Financial support 3. To compare the administrative processes of Catholic and Protestant private schools. Method and Procedure The researcher used books, journals and other research documents as the basis for formulating the questionnaire to be utilized in conduction interviews. The questionnaire was pretested at 3 types of parochial private schools: 1. Parish Schools administered by Catholic priests. 2. Schools administered by a Catholic religious order. 3. Schools administered by the Protestant Church. The pretested questionnaire was used in interviewing the Director of the school and one Department Head at each of the three types of parochial schools listed above. After pretesting, the contents and structure of the questionnaire were analyzed and revised prior to their application to 23 parochial private schools in Bangkok & Thonburi. In each school the Director and one Head of Department were interviewed and the contents subsequently tabulated and analyzed by means of percentage. Findings and Conclusions: 1. Listed in order of importance, the philosophy and objective of the parochial private schools in Bangkok and Thonburi appear to be: 1.1 To develop the student in all the four phases of education, namely: moral, physical, intellectual, and manual. 1.2 To develop a sense of good citizenship to the end that the student may be conscious of their obligations and made himself useful to society. 1.3 To develop a religious belief as a basis for the way of life. 1.4 To develop individualty. 2. The organizational system of parochial private schools exihibits the following characteristics: 2.1 The following difference between line and staff responsibility in Catholic and Protestant schools were noticed:- 2.1.1 In Catholic school line responsibility is delegated from the parish priest to the School Director and from the latter to his staff. 2.1.2 In Protestant school line responsibility is delegated by a Board of Directors or School Board to the Director of the school. 2.2 Control of parish Catholic schools is in the hands of parish priests and above them, the Archbishop. In schools administered by a religious order control is exercised by the Order’s Superior. In Protestant schools it is exercised by a Board of Directors or a Schools Board. 2.3 Management and operation are conducted in accordance with foreign examples and models. Catholic schools are generally more conservative and Protestant schools more progressive. 2.4 Financial support generally comes from the following sources: borrowings from the religious organizations; charities; alumni support; profits from land sales or rents; boarding student; special tuition. 3. Comparison of Catholic and Protestant administrative processes within their respective schools: 3.1 Catholic schools generally use staff responsibility for long range planning; Protestant schools achieve this end through line responsibility. 3.2 Catholic schools generally lack a handbook to guide them in their organizational structure. 3.3 In general, both Catholic and Protestant systems use the merit system for selection and developing their staff. However, Catholic schools take into consideration the staff’s experience while Protestant schools consider also the staff’s religious affiliation. Protestant schools generally send their staff members abroad for study tours more than Catholic schools do. Promotion within the Protestant schools is handled by a Board of Directors while the Catholic system relies on the Religious Superior. 3.4 In Protestant schools, direction emanates from the Board of Directors or the School Board; in Catholic schools direction is from the school Director or the Religious Superior. 3.5 In the Protestant system there is more parental participation (through parent membership in the School Board or Board of Directors) than in the Catholic system. 3.6 In general, the Protestant system gives greater attention to analyzing student achievements as a means of improving the school system than does the Catholic System. 3.7 Both Protestant and Catholic systems generally rely on the annual budget planning though some Catholic institutions do not. In most cases both the systems depend on school fees to pay for 90 per cent of the teachers’ salaries.